High Performance in Complex Spatial Systems: A Self-Organizing Mapping Approach with Reference to The Netherlands - Karima Kourtit; Daniel Arribas-Bel; Peter Nijkamp (Tinbergen Institute, 2013)
This paper addresses the performance of creative firms from the perspective of complex spatial systems. Based on an extensive high-dimensional database on both the attributes of individual creative firms in the Netherlands and a series of detailed regional facilitating and driving factors related, inter alia, to talent, innovation, skills, networks, accessibility and hardware, a new methodology called self-organizing mapping (SOM) is applied to identify and explain in virtual topological space, the relative differences between these firms and their business performance in various regions. It turns out that there are significant differences in the spatial and functional profile of large firms vis-à-vis SMEs across distinct geographical areas in the country.
Keywords: M1; Q5; R1; R10; 330; complex spatial systems; self-organizing mapping; creative firms; talent; innovation; networks; accessibility; business performance; spatial and functional profiles; SMEs; large firms; geographical areas